COVID‐19 in lung transplant patients: A case series. Issue 11 (29th August 2020) - Verleden, Geert M.; Godinas, Laurent; Lorent, Natalie; Van Bleyenbergh, Pascal; Dupont, Lieven; Delcroix, Marion; Yserbyt, Jonas; Dooms, Christophe; Vos, Robin
Abstract : Several case reports and small case series have been published on coronavirus disease 2019 infection after solid organ transplantation; however, thus far there are limited data on coronavirus disease 2019 infections in lung transplant patients. In the present single‐center case series we discuss 10 lung transplant patients with a documented severe acute respiratory syndrome coronavirus 2 infection, diagnosed with nasopharyngeal swab in 8 and bronchoalveolar lavage in 2. Eight of 10 patients needed hospital admission, of whom 1 was in the intensive care unit. He died after 2 weeks from multiple organ failure. The remaining nine patients recovered. Cell cycle inhibitors were withheld in all patients, whereas the calcineurin inhibitor and corticosteroids were continued at the same dose, with an acceptable outcome. Abstract : This case series describes the symptomatology, risk factors, treatment, and outcome of lung transplant recipients with documented SARS‐CoV‐2 infection.